2016
DOI: 10.18632/oncotarget.8020
|View full text |Cite
|
Sign up to set email alerts
|

MiR-448 promotes glycolytic metabolism of gastric cancer by downregulating KDM2B

Abstract: MicroRNAs are critical in various human cancers, including gastric cancer (GC). However, the mechanism underlying the GC development remains elusive. In this study, we demonstrate that miR-448 is increased in GC samples and cell lines. Overexpression of miR-448 facilitated the proliferation of GC cells by stimulating glycolysis. Mechanistically, we identified KDM2B, a reader for methylated CpGs, as the target of miR-448 that represses glycolysis and promotes oxidative phosphorylation. Overexpression of miR-448… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…It has been reported that deletion of G-protein-coupled receptor-48 (GPR48) led to decreased expression of KDM2B through cAMP-CREB pathway [49]. Furthermore, miR-448 and miR-146a-5p could also regulate the expression of KDM2B [50,51]. However, the mechanism of increased expression of KDM2B in PDAC has not been revealed, which could be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that deletion of G-protein-coupled receptor-48 (GPR48) led to decreased expression of KDM2B through cAMP-CREB pathway [49]. Furthermore, miR-448 and miR-146a-5p could also regulate the expression of KDM2B [50,51]. However, the mechanism of increased expression of KDM2B in PDAC has not been revealed, which could be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the JmjC domain is the active center that can catalyze the demethylation of H3K36me2 and H3K4me3 2831. Recently, some studies have suggested that KDM2B regulates gene expression in a JmjC-dependent manner and may be involved in tumorigenesis; thus, it has gradually received increasing research attention 25,32. KDM2B overexpression in mouse embryonic fibroblasts (MEFs) induces cellular proliferation and inhibits apoptosis, leading to the immortalization of normal cells 7…”
Section: Discussionmentioning
confidence: 99%
“…If abnormal JmjC demethylase activity is modulated, it can lead to normal transcriptional arrangements. Therefore, JmjC domain inhibitors might have therapeutic potentials for the treatment of cancer [24,25,26,27].…”
Section: Discussionmentioning
confidence: 99%